The Old Order Of Captivity Of Sin And Death: A Man Before Coming Of Christ - Misztal, Wojciech (Studia Theologica Varsaviensia, 2020)
$e wordings presented by us do not belong to the most popular either in the New Testament or in the afore-mentioned so-called authentic epistles of St. Paul the Apostle. It does not mean, however, that they do not have those meanings. God’s word, also by their assistance, tells us about our human life. At this current stage, we did not manage to possess this gi~ in full, which eternally stays with God, or eternal salvation. Simultaneously, we are aware, however, that together with the coming of Christ, our situation radically changed for the better. We are not slaves anymore of such powers as sin or death. It is true that our liberation is neither complete nor final yet. We cannot go to the other extreme, however, and not to admit that we do not belong to them, that Life stays behind us, that He is already an absolute Lord now and Lord of us, ourselves and of all this, which was created (cf. e.g. Philippians %:&2). In other words, following the Apostle of nations, we could describe our current situation in the following way. As Christians we are already in Christ (Greek: en Christô). In temporality, however, we are the successors of Adam: just as if our fates became “closed”, “programmed” in Adam. We remain beings limited by Death. We still and continually experience a frightening burden of its reign. Repeating the words of St. Paul we may reflect this aspect of our existence in temporality, reaching for the expression “in death” as we still belong in its zone. We also “live” in it in some way. However, this is not everything. Our temporal life also has other aspects. $us, to reflect on them, the Apostle will refer to the mystery of law / Law and to the mystery of what is material, in particular in man himself, to the mystery of thebody (Greek: sôma and sarx). As we noticed, also the last three may be something negative, captivating a man, not least serving for his good. A man, waiting for his meeting with Christ, or already living with this meeting, is also a living being, also in a pejorative sense, in body (en sômati and en sarki). We can state the same about another of God’s gi~s, about law / Law, as well as about order, which the Apostle reflects on by the expression “in law” / “in Law”. As we noticed, such a defined image is not unanimously negative. A man living in a described situation has not lost his chance yet. He needs salvation and may obtain it. When it occurs, his situation changes. $e transition is radical, although usually a given person gradually experiences it. It is o~en divided into their entire life. Most frequently the old order does not disappear at once. It becomes partially abolished, annihilated. It partially becomes transformed, cured. It partially influences us as well. Our temporality is such. And just as such, it constitutes time and place of salvific work of God and an integral part of the Divine economy. And it frequently outgrows our potential of understanding, reminding us at the same time about the place and role of faith, hope and love. One of the aspects of the Pauline vision of salvific work could be presented in a great outline in this way. It is noticeable in a specific, interesting way in the wordings we come across in e.g. the so-called authentic epistles of St. Paul the Apostle. $is, expressed by them, being God’s Word, refers not only to people living in the Apostle’s time. It concerns people of all times. It concerns us also.